Ketentuan Batas Waktu Usia Kehamilan Akibat Pemerkosaan Sebagai Syarat Abortus Provocatus Criminalis - Alvira Damayanti; Ade Adhari (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2022)
One of the most highlighted cases of sexual violence in recent times is the rise of criminal cases of rape against teenagers and minors. Most of the rape victims will experience trauma, psychological disorders and even pregnancy, causing an abortion. The time limit for gestational age due to rape as a condition for abortion provocatus criminalis needs to be analyzed and revised. This research method is empirical research. Based on the results of the study that the time to be able to carry out an abortion needs to be evaluated by the government because for rape victims 6 weeks is a very short time. The ideal form of analysis and revision of the time limit for gestational age due to rape as a condition for abortion provocatus criminalis should be 12 weeks-24 weeks.